Steel coil for photovoltaic bracket and preparation method of steel coil
By optimizing the preparation process and chemical composition of the steel coil, a high-strength, corrosion-resistant steel coil for photovoltaic brackets is formed, which solves the cost and performance problems caused by high precious alloy elements and achieves efficient and environmentally friendly photovoltaic bracket production.
Patent Information
- Application Number
- CN202411314080.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-20
AI Technical Summary
The existing steel for photovoltaic brackets has high content of precious alloy elements, which increases production costs, and the comprehensive performance of steel is poor, which has problems such as high production difficulty and low production efficiency.
The steel coils for photovoltaic brackets are prepared by pretreatment, heating and insulation treatment, rough rolling and finishing rolling and cooling treatment, and the content of chemical components such as C, Si, Mn, P, S, Cu, Cr, Ti, Al is controlled. Form ferrite and martensite microstructure to improve the tensile strength and corrosion resistance of steel.
It realizes high-strength, lightweight, high hole expansion, high corrosion resistance, low cost, high efficiency, coating-free, maintenance-free, energy-saving and environmentally friendly photovoltaic bracket production, reducing processing difficulty and production costs.
Smart Images

Figure CN119194288A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hot-rolled steel strip manufacturing, and specifically relates to a steel coil for a photovoltaic support and a preparation method thereof. Background Art
[0002] The steel used for photovoltaic brackets is currently mainly based on plain carbon steel, and hot-dip galvanizing or zinc-aluminum-magnesium is used to improve corrosion resistance. However, hot-dip galvanizing or zinc-aluminum-magnesium will pollute the environment, increase production processes, prolong the process flow, and increase manufacturing costs; and the coating can be easily damaged during transportation and processing, causing corrosion to the substrate, and subsequent maintenance is necessary to avoid premature failure.
[0003] Photovoltaic brackets made of weathering steel have a dense protective rust layer formed on the surface during service, which greatly improves their corrosion resistance. The rust layer can heal itself after damage, and there is no need for subsequent pickling, painting and maintenance. Therefore, the use of weathering steel to manufacture photovoltaic brackets has the advantages of environmental protection, energy saving, high efficiency and low cost. However, most of the existing weathering steels have added precious alloy elements such as Ni and Nb, which have high alloy costs, insufficient corrosion resistance, poor hole expansion performance, and low competitiveness, which is not conducive to large-scale promotion and application.
[0004] The prior art discloses a low-cost 650MPa-grade titanium-containing weathering steel for a photovoltaic bracket and a preparation method thereof, wherein the chemical composition of the titanium-containing weathering steel includes: C: ≤0.08%, Si: 0.35%-0.50%, Mn: 0.40%-0.60%, P: 0.08%-0.12%, S: ≤0.010%, Cu: 0.25%-0.40%, Cr: 0.75%-1.00%, Ti: 0.065%-0.105%, N: ≤0.0050%, and the rest is Fe and unavoidable impurities. The titanium-containing weathering steel has a thickness of 1.5-4.0 mm, an I index of 7.54-9.04, a tensile strength of 683-705 MPa, and an elongation after fracture of 23.5-26%. However, the higher P content in the above-mentioned photovoltaic bracket steel will cause serious segregation of the ingot, reduce the plasticity, low-temperature toughness and welding performance of the steel, and easily cause hydrogen-induced cracking, stress corrosion cracking and surface cracking, aggravating intergranular corrosion. At the same time, the precious alloy element Cu content in the above-mentioned photovoltaic bracket steel is relatively high, the product cost is high and it is easy to produce network crack defects during hot rolling. The Ti content is high, and the coarse TiN precipitates formed are easy to become stress concentration points and microcrack sources, which will correspondingly reduce the forming and fatigue performance of the photovoltaic bracket; the recovery rate of Ti is unstable, and the mechanical properties fluctuate greatly, which will correspondingly increase the difficulty of photovoltaic bracket processing and reduce processing efficiency. At the same time, the above-mentioned photovoltaic bracket steel lacks data such as hole expansion performance and forming performance, making it difficult for users to select materials.
[0005] The prior art discloses a low-cost 650MPa-level antimony-containing weathering steel for photovoltaic brackets and a preparation method thereof, wherein the chemical composition of the antimony-containing weathering steel includes: C: ≤0.08%, Si: 0.35%-0.50%, Mn: 0.40%-0.60%, P: 0.08-0.12%, S: ≤0.010%, Cu: 0.25%-0.40%, Cr: 0.75%-1.00%, Ti: 0.065%-0.105%, N: ≤0.0050%, Sb: 0.05%-0.07%, and the rest is Fe and unavoidable impurities. The thickness of the antimony-containing weathering steel is 1.5-4.0mm, the I index is 7.67-9.04, the tensile strength is 680-700MPa, and the elongation after fracture is 23.5-26%. However, the higher P content in the above photovoltaic bracket steel will cause serious segregation of the ingot, reduce the plasticity, low temperature toughness and welding performance of the steel, easily cause hydrogen-induced cracking, stress corrosion cracking and surface cracking, and aggravate intergranular corrosion. At the same time, the content of precious alloy element Cu is high, the product cost is high and it is easy to produce network crack defects during hot rolling. The Ti content is high, and the coarse TiN precipitates formed are easy to become stress concentration points and microcrack sources, which will correspondingly reduce the forming and fatigue performance of the photovoltaic bracket; the recovery rate of Ti is unstable, and the mechanical properties fluctuate greatly, which will correspondingly increase the difficulty of photovoltaic bracket processing and reduce processing efficiency. Not only that, Sb in the above photovoltaic bracket steel is one of the five harmful elements, which is easy to cause central segregation of the ingot, it is easy to segregate at the grain boundary, weaken the grain boundary, increase the tendency of brittle fracture along the crystal, and correspondingly significantly reduce the impact toughness and forming performance of the steel. It is easy to precipitate and enrich between the steel matrix and the oxide layer, increase the tendency of hot brittleness, and correspondingly deteriorate the surface quality of the steel strip. At the same time, the above photovoltaic bracket steel lacks data such as hole expansion performance and forming performance, making it difficult for users to select materials.
[0006] The prior art also discloses a 650MPa grade high weathering steel for photovoltaic brackets and a preparation method thereof, wherein the chemical composition of the high weathering steel includes: C: ≤0.08%, Si: 0.20%-0.30%, Mn: 0.40%-0.60%, P: ≤0.02%, S: ≤0.010%, Cu: 0.20%-0.40%, Cr: 2.50%-3.00%, Ni: 0.20%-0.30%, Nb: 0.005%-0.015%, Ti: 0.050%-0.090%, N: ≤0.0050%, and the rest is Fe and unavoidable impurities. The thickness of the high weathering steel is 1.5mm-4.0mm, the I index is 8.11-9.59, the tensile strength is 675-705MPa, and the elongation after fracture is 24-26%. However, the precious alloy element Cu content in the above photovoltaic bracket steel is relatively high, the product cost is high and it is easy to produce network crack defects during hot rolling. In addition, the addition of precious alloy elements such as Ni and Nb increases the alloy cost. The Ti content is relatively high, and the coarse TiN precipitates formed are easy to become stress concentration points and microcrack sources, which will correspondingly reduce the forming and fatigue performance of the photovoltaic bracket. The recovery rate of Ti is unstable and the mechanical properties fluctuate greatly, which will correspondingly increase the difficulty of photovoltaic bracket processing and reduce processing efficiency. At the same time, the above photovoltaic bracket steel lacks data such as hole expansion performance and forming performance, making it difficult for users to select materials.
[0007] It can be seen from this that the content of precious metal elements in the steel used for photovoltaic brackets in the existing technology is relatively high, which increases production costs, and the comprehensive performance of the steel is relatively poor. At the same time, there are also problems such as high production difficulty and low production efficiency, which need to be improved. Summary of the invention
[0008] In order to solve all or part of the above problems, the purpose of the present invention is to provide a steel coil for photovoltaic brackets and a preparation method thereof. The preparation method of the present invention has low difficulty in producing hot-rolled steel coils; the obtained steel coil has good hole expansion performance, high strength and excellent corrosion resistance.
[0009] According to one aspect of the present invention, there is provided a method for preparing a steel coil for a photovoltaic support, comprising:
[0010] Obtaining a continuous casting billet through pretreatment;
[0011] Heating and heat-insulating the continuous casting billet;
[0012] Rough rolling the continuous casting billet using a rough rolling mill to obtain a strip billet;
[0013] Using a finishing mill to finish-roll the strip to obtain a hot-rolled steel strip; and
[0014] Cooling the hot-rolled steel strip, and coiling the cooled hot-rolled steel strip into a steel coil;
[0015] Wherein, the continuous casting billet comprises the following components by mass percentage:
[0016] C: 0.08%-0.10%, Si: 0.55%-0.64%, Mn: 0.51%-0.60%, P: 0.056%-0.065%, S: 0.0050%-0.0060%, Cu: 0.13%-0.18%, Cr: 2.8%-3.0%, Ti: 0.026%-0.035%, Alt: 0.17%-0.20%, and the rest are Fe and unavoidable impurities, and the continuous casting billet also needs to satisfy C+2P≤0.30%.
[0017] Furthermore, the method of obtaining the continuous casting billet by pretreatment specifically comprises: obtaining the continuous casting billet by desulfurization of molten iron pretreatment, top and bottom composite blowing converter smelting, LF refining and slab continuous casting; the thickness of the continuous casting billet is 180-230 mm.
[0018] Furthermore, the heating and heat preservation treatment of the continuous casting billet further comprises: loading the continuous casting billet into a walking beam heating furnace; and heating and heat preservation treatment of the continuous casting billet in the walking beam heating furnace;
[0019] The furnace discharge temperature of the continuous casting billet is 1190-1210° C., and the cumulative furnace residence time of the continuous casting billet is 180-210 minutes.
[0020] Further, the step of rough rolling the continuous casting billet with a rough rolling mill to obtain a strip billet is as follows: the starting rolling temperature of the rough rolling is controlled to be 1140-1160° C., the final rolling temperature of the rough rolling is controlled to be 1070-1110° C., and the continuous casting billet is rolled with a rough rolling mill to obtain a strip billet;
[0021] The thickness of the strip obtained by the rough rolling is 28-40 mm, the number of rough rolling passes is 7, and the cumulative reduction rate of the rough rolling is 82.6-87.8%.
[0022] Further, the use of a finishing mill to perform finish rolling on the strip to obtain a hot-rolled steel strip is specifically as follows: controlling the start rolling temperature of the finishing rolling to be 1010-1060° C., the final rolling temperature of the finishing rolling to be 860-900° C., and using a finishing mill to perform finish rolling on the strip to obtain a hot-rolled steel strip;
[0023] The thickness of the hot-rolled steel strip obtained by the finish rolling is 1.5-4.0 mm, the finish rolling adopts a 7-stand finish rolling unit, and the cumulative reduction rate of the finish rolling is 90-94.3%.
[0024] Furthermore, the hot-rolled steel strip is cooled and the cooled hot-rolled steel strip is coiled into a steel coil, specifically: the hot-rolled steel strip transported on a laminar cooling roller is cooled; and the coiling temperature is controlled to be 170-210°C, and the cooled hot-rolled steel strip is coiled into a steel coil by a coiler.
[0025] Furthermore, the cooling treatment of the hot-rolled steel strip transported on the laminar cooling roller is specifically as follows:
[0026] The hot-rolled steel strip transported on the laminar cooling roller is subjected to the first stage of water cooling at a cooling rate of ≥110°C / S to cool the steel strip to 660-690°C; after air cooling for 3-5S, the air-cooled steel strip is subjected to the second stage of water cooling at a cooling rate of ≥100°C / S.
[0027] The present invention also provides a steel coil for a photovoltaic support, which is prepared by any one of the preparation methods described above.
[0028] Furthermore, the microstructure of the steel coil is ferrite and martensite, wherein the ferrite ratio is 70-90% and the martensite ratio is 10-30%;
[0029] The yield strength of the steel coil is ≥550MPa, the tensile strength is ≥650MPa, the yield strength ratio is ≤0.80, and the elongation after fracture is ≥25%;
[0030] After the steel coil is periodically immersed in a NaHSO3 solution with an initial concentration of 0.01 mol / L for 72 hours, the corrosion rate relative to Q355B ordinary steel is ≤28%;
[0031] The straight seam electric welded steel pipe processed from the steel coil has no cracks in the base material during the 60° expansion test.
[0032] It can be seen from the above technical solution that the photovoltaic support steel coil and the preparation method thereof provided by the present invention have the following beneficial effects:
[0033] The steel coil prepared by the preparation method of the present invention can better meet the new requirements for the development of photovoltaic brackets such as high strength, light weight, high hole expansion, high corrosion resistance, long life, easy manufacturing, low cost, high efficiency, painting-free, maintenance-free, energy-saving, and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The accompanying drawings are incorporated in and constitute a part of this specification and, together with the description, serve to explain the principles of the present invention.
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0036] Figure 1 A flow chart of a preparation method according to an embodiment of the present invention;
[0037] Figure 2 A schematic diagram of a straight seam electric welded steel pipe sample obtained by using a steel coil according to an embodiment of the present invention and subjected to a 60° expansion test, and a parent material after the test. DETAILED DESCRIPTION
[0038] In order to fully understand the purpose, features and effects of the present invention, the present invention is described in detail through the following specific embodiments. Except for the following contents, the process method of the present invention adopts conventional methods or devices in the art. Unless otherwise specified, the following terms have the meanings commonly understood by those skilled in the art.
[0039] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe a feature or characteristic, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0040] A method for preparing a steel coil for a photovoltaic support according to an embodiment of the present invention, such as Figure 1 As shown, including:
[0041] Step S001: obtaining a continuous casting billet through pretreatment;
[0042] Step S002: heating and heat-insulating the continuous casting billet;
[0043] Step S003: rough rolling the continuous casting billet using a rough rolling mill to obtain a strip billet;
[0044] Step S004: using a finishing mill to finish-roll the strip to obtain a hot-rolled steel strip; and
[0045] Step S005: cooling the hot-rolled steel strip, and coiling the cooled hot-rolled steel strip into a steel coil;
[0046] Wherein, the continuous casting billet in step S001 includes the following components by mass percentage:
[0047] C: 0.08%-0.10%, Si: 0.55%-0.64%, Mn: 0.51%-0.60%, P: 0.056%-0.065%, S: 0.0050%-0.0060%, Cu: 0.13%-0.18%, Cr: 2.8%-3.0%, Ti: 0.026%-0.035%, Alt: 0.17%-0.20%, and the rest are Fe and unavoidable impurities.
[0048] The tensile strength of the steel coil prepared by the preparation method of the embodiment of the present invention is above 650 MPa, and has good hole expansion performance.
[0049] The reasons for limiting the chemical elements in the embodiments of the present invention are as follows:
[0050] It has been found in practice that adding C to steel is an effective and economical method to improve the strength of steel. An appropriate amount of C combined with Ti can form TiC nano-scale precipitates, which have significant fine grain strengthening and precipitation strengthening effects. However, with the increase of C content, the plasticity, hole expansion performance, impact toughness, welding performance, forming performance, and corrosion resistance of steel will decrease. In order to make the tensile strength of the steel strip of the embodiment of the present invention reach more than 650MPa, and comprehensively consider the processing performance, welding performance and corrosion resistance, while taking into account the economy, the embodiment of the present invention controls the C content in the range of 0.08%-0.10%.
[0051] Si is not a precious alloying element. It has been found in practice that its solid solution strengthening coefficient in ferrite is higher than that of Mn, which can effectively improve the strength of steel and improve corrosion resistance. However, too high Si content will reduce the toughness of the material and is not conducive to improving welding performance. In order to make the tensile strength of the steel strip of the embodiment of the present invention reach more than 650MPa, and comprehensively consider the processing performance, welding performance and corrosion resistance, while taking into account the economy, the embodiment of the present invention controls the Si content in the range of 0.55%-0.64%.
[0052] It has been found in practice that Mn has a solid solution strengthening effect in steel, which increases the strength of the steel linearly. Mn is an austenite-forming element, which has the effect of stabilizing austenite, can reduce the austenite transformation temperature (Ar3), increase the ferrite nucleation rate, and reduce the grain growth rate, that is, it has the effect of refining the grains. However, as the Mn content increases, the C equivalent of the steel increases, which is not good for welding performance. In order to make the tensile strength of the steel strip of the embodiment of the present invention reach more than 650MPa, and comprehensively consider the processing performance and welding performance, while taking into account the economy, the embodiment of the present invention controls the Mn content in the range of 0.51%-0.60%.
[0053] It has been found in practice that the solid solution strengthening effect of P in steel is second only to C, and it can also effectively improve the atmospheric corrosion resistance of steel. Among the many alloy elements that improve corrosion resistance, P is the most cost-effective element. However, P is easy to form and precipitate Fe3P in steel, which increases the brittleness of steel and is not conducive to improving the welding performance of steel. The diffusion rate of P in γ iron and α iron is low, and it is easy to form segregation, which has an adverse effect on the forming performance of steel. In order to make the tensile strength of the steel strip of the embodiment of the present invention reach more than 650MPa, and comprehensively consider the processing performance, welding performance and corrosion resistance, while taking into account the economy, the embodiment of the present invention controls the P content in the range of 0.056%-0.065%.
[0054] It has been found in practice that a higher S content can cause "hot brittleness" defects in steel. Adding Mn and S to the steel to form MnS plastic inclusions is an effective measure to reduce the harmful effects of S. However, during the rolling process, MnS extending along the rolling direction is prone to form a banded structure, which will reduce the transverse impact toughness and forming properties of the steel strip, and at the same time lead to anisotropy of mechanical properties. S is harmful to the corrosion resistance of steel, and sulfides in steel can become the source of rust. Therefore, the S content should be reduced as much as possible, but if the S content is controlled too low, it will increase manufacturing costs and reduce production efficiency. Taking into account the uniformity of mechanical properties, processing properties and corrosion resistance of the high-expansion steel strip in the embodiment of the present invention, while taking into account economy and production efficiency, the S content in the embodiment of the present invention is controlled in the range of 0.0050%-0.0060%.
[0055] It has been found in practice that Cu can form a dense amorphous oxide protective layer on the surface of steel, thereby effectively improving the corrosion resistance of steel. However, Cu has a low melting point (1083°C), and is easily segregated at the grain boundary during the heating process of the continuous casting billet. Too high a Cu content will cause a network crack defect during hot rolling. Cu is also a relatively precious alloy element, and too high a Cu content will lead to increased product costs. Taking into account the hot working performance, surface quality and corrosion resistance of the high hole expansion steel strip in the embodiment of the present invention, while taking into account the economy, the Cu content in the embodiment of the present invention is controlled in the range of 0.13%-0.18%.
[0056] It has been found in practice that Cr has a solid solution strengthening effect, which can improve the hardenability and strength of steel, form a dense and uniform rust layer containing fine α-FeOOH on the surface of the substrate, accelerate the development of electrochemical corrosion products to a thermodynamically stable state, block the further penetration of corrosive media into the substrate, and reduce the corrosion rate of steel. However, when the Cr content is too high, carbides will precipitate at the grain boundaries, reduce the plasticity and toughness of the steel, and correspondingly deteriorate the forming and welding properties, and increase the alloy cost. In order to make the tensile strength of the steel strip of the embodiment of the present invention reach more than 650MPa, and comprehensively consider the corrosion resistance, plasticity and toughness, processing performance, welding performance, and economic efficiency, the embodiment of the present invention controls the Cr content in the range of 2.8%-3.0%.
[0057] It has been found in practice that TiN formed by Ti and N can inhibit the growth of austenite grains during the heating process of the continuous casting billet, which is beneficial to improving the strength and toughness and welding performance of the steel. Ti and C form nano-scale TiC precipitates during the hot rolling process, which have fine grain strengthening and precipitation strengthening effects, and can improve the strength and toughness of the steel. However, if the Ti content is high, on the one hand, coarse TiN precipitates are easily formed, and become stress concentration points and microcrack sources, reducing the forming and fatigue performance of the photovoltaic bracket. On the other hand, the recovery rate of Ti is unstable and the mechanical properties fluctuate greatly. Therefore, too high a Ti content will increase the difficulty of photovoltaic bracket processing and reduce processing efficiency. Taking into account the strength and toughness, welding performance, processing performance and use performance of the high-expansion steel belt in the embodiment of the present invention, the embodiment of the present invention controls the Ti content in the range of 0.026%-0.035%.
[0058] It has been found in practice that the fine AlN formed by Al and N can inhibit the growth of austenite grains during the heating process of the continuous casting billet, has the effect of refining grains, and can improve the strength, toughness and welding performance of steel. In the marine atmosphere environment, Al and Si work synergistically, so that the generated rust layer has a strong barrier effect against corrosive media and moisture. However, too high an Al content will lead to the formation of more Al2O3 inclusions, which on the one hand will reduce the purity of the steel and the impact performance, corrosion resistance and surface quality of the steel strip, and on the other hand, it is very easy to block the water nozzle during continuous casting, increase the difficulty of production, reduce production efficiency, and increase the alloy cost and manufacturing cost. Taking into account the strength, welding performance, processing performance, corrosion resistance and surface quality of the high-expansion steel strip in the embodiment of the present invention, and taking into account the difficulty of production, production efficiency and economy, the embodiment of the present invention controls the Alt content in the range of 0.17%-0.20%.
[0059] The continuous casting in step S001 also needs to satisfy C+2P≤0.30%.
[0060] It has been found in practice that P is an element that is easily segregated in steel, and its hardenability in the segregation zone is about twice that of C. If C+2P>0.30, as C+2P increases, the strength and hardness of the steel increase linearly, and the plasticity and hole expansion performance decrease; if C+2P≤0.30%, the influence of C+2P on the mechanical properties and hole expansion performance of the steel slows down. Therefore, considering the comprehensive mechanical properties of the high hole expansion steel strip in the embodiment of the present invention, the embodiment of the present invention controls C+2P≤0.30%.
[0061] The above-mentioned C, Si, Mn, P, S, Cu, Cr, Ti, Alt element contents and the selection of C+2P have a synergistic effect. By controlling the content of each element and C+2P within the above-mentioned range, the solid solution strengthening, fine grain strengthening and phase transformation strengthening effects can be fully exerted, so that the low-alloy corrosion-resistant steel for photovoltaic brackets has high hole expandability, high purity, high strength and excellent cold processing performance.
[0062] The selection of the above-mentioned Si, P, S, Cu, Cr, and Alt element contents has a synergistic effect. By controlling the content of each element within the above-mentioned range, a dense inner rust layer can be formed on the surface of the steel matrix, so that the high-expansion low-alloy corrosion-resistant steel for photovoltaic brackets has high corrosion resistance and can meet service requirements. It does not require subsequent pickling, painting and maintenance, and is energy-saving and environmentally friendly.
[0063] The selection of the above-mentioned C, Mn, S, Cu and Alt has a synergistic effect. By controlling the content of each element within the above-mentioned range, defects such as hot-rolled network cracks can be avoided, so that the high-expansion low-alloy corrosion-resistant steel for photovoltaic brackets has excellent hot processing properties and high surface quality, which can meet the stringent processing and service requirements of photovoltaic brackets.
[0064] The selection of all the above-mentioned element contents and C+2P has a synergistic effect. By controlling the contents of all the elements and C+2P within the above-mentioned ranges, the high-expansion low-alloy corrosion-resistant steel for photovoltaic brackets has low processing difficulty, high production efficiency, low manufacturing cost and short delivery cycle.
[0065] Among them, step S001 obtains the continuous casting billet through pretreatment, specifically: obtains the continuous casting billet through molten iron pretreatment desulfurization, top and bottom composite blowing converter smelting, LF refining and slab continuous casting; the thickness of the continuous casting billet is 180-230mm.
[0066] It has been found in practice that, under the premise of determining the width and length of the continuous casting billet, the thicker the continuous casting billet, the higher the output and yield rate, but the greater the mill load, the greater the fluctuation of the final rolling temperature, microstructure and mechanical properties of the finished steel strip in the length direction, and the thickness of the continuous casting billet is also limited by the maximum outer diameter of the steel coil allowed by the coiler. Taking the above influences into consideration, the embodiment of the present invention controls the thickness of the continuous casting billet to be 180-230mm.
[0067] Among them, step S002 of heating and keeping the continuous casting billet warm further includes: loading the continuous casting billet into a walking-beam heating furnace; and heating and keeping the continuous casting billet in the walking-beam heating furnace warm; the furnace discharge temperature of the continuous casting billet is 1190-1210°C, and the cumulative furnace residence time of the continuous casting billet is 180-210 minutes.
[0068] It has been found in practice that if the furnace temperature of the continuous casting billet is lower than 1190°C, the austenite grains can be refined, but the thermoplasticity of the continuous casting billet is poor, the deformation resistance is high, and the thermal deformation is difficult, which will lead to a low subsequent rolling mill operating rate; if the furnace temperature of the continuous casting billet is higher than 1210°C, although the thermoplasticity of the continuous casting billet is improved, the deformation resistance is reduced, and it is easy to be thermally deformed, the corresponding subsequent rolling mill operating rate will be improved, but the austenite grains are easy to coarsen. Taking the above effects into consideration, the embodiment of the present invention controls the furnace temperature of the continuous casting billet to be 1190-1210°C.
[0069] If the cumulative residence time of the continuous casting billet is shorter than 180 minutes, its structure is not easy to be homogenized, the rolling energy consumption is high, and equipment accidents are prone to occur; if the cumulative residence time of the continuous casting billet is longer than 210 minutes, it is easy to be oxidized, burned and decarburized, which will increase energy consumption accordingly, and reduce the mill operation rate and production efficiency. Taking the above effects into consideration, the embodiment of the present invention controls the cumulative residence time of the continuous casting billet to 180-210 minutes.
[0070] Among them, step S003 uses a rough rolling mill to rough roll the continuous casting billet to obtain a strip billet. Specifically, the starting rolling temperature of the rough rolling is controlled to be 1140-1160°C, the final rolling temperature of the rough rolling is controlled to be 1070-1110°C, and the continuous casting billet is rolled by the rough rolling mill to obtain a strip billet.
[0071] It has been found in practice that the main metallurgical purpose of rough rolling is to destroy the as-cast structure of the continuous casting billet, effectively refine the austenite grains through multiple recrystallizations, and obtain an austenite structure with uniform and fine grains. If the rough rolling start temperature is too high, uneven austenite grains will occur, resulting in differences in the strip structure and affecting the uniformity of the mechanical properties of the finished product. If the rough rolling start temperature is too low, the strip shape control becomes more difficult, the mill load and rolling energy consumption increase, and it is not conducive to smooth rolling. Taking the above influences into consideration, the embodiment of the present invention controls the rough rolling start temperature to 1140-1160°C, and the rough rolling final rolling temperature to 1070-1110°C.
[0072] The thickness of the strip obtained by the rough rolling is 28-40 mm, the number of rough rolling passes is 7, and the cumulative reduction rate of the rough rolling is 82.6-87.8%.
[0073] It has been found in practice that if the strip is too thick and the cumulative reduction rate of rough rolling is too small, partial recrystallization is likely to occur, causing mixed crystal phenomenon, which has an adverse effect on the uniformity of the mechanical properties of the finished steel strip, and at the same time will increase the rolling load and rolling energy consumption of the finishing mill, affecting the stability of finishing rolling. If the strip is too thin and the cumulative reduction rate of rough rolling is too large, it is not conducive to improving the strip shape quality, and will increase the rolling load and rolling energy consumption of the rough rolling mill, which is not conducive to the smooth rolling. At the same time, it is impossible to ensure the finishing rolling start temperature required for rolling the 1.5-4.0mm thin finished steel strip of the present invention, and it may even increase the rolling load and rolling energy consumption of the finishing mill. Taking the above effects into consideration, the embodiment of the present invention controls the strip thickness to be 28-40mm and the cumulative reduction rate of rough rolling to be 82.6-87.8%. According to the rough rolling mill force and energy parameters, the continuous casting billet and the strip thickness, it can be calculated that the reasonable rolling pass of the rough rolling mill is 7 passes.
[0074] Among them, step S004 uses a finishing mill to finish rolling the strip to obtain a hot-rolled steel strip. Specifically, the starting rolling temperature of the finishing rolling is controlled to be 1010-1060°C, the final rolling temperature of the finishing rolling is 860-900°C, and the finishing mill is used to finish rolling the strip to obtain a hot-rolled steel strip.
[0075] It has been found in practice that if the finishing rolling start temperature is too high, partial recrystallization will easily occur in the first stand (F1) and the second stand (F2), resulting in mixed crystal problems and differences in the finished steel strip structure and abnormal fluctuations in mechanical properties; if the finishing rolling start temperature is too low, the desired final rolling temperature cannot be guaranteed. Taking the above factors into consideration, the finishing rolling start temperature is controlled to be 1010-1060°C in the embodiment of the present invention.
[0076] It has been found in practice that if the finishing rolling temperature is too high, the finished steel strip will be coarsened and the toughness will be reduced; if the finishing rolling temperature is too low, the strength of the finished steel strip will be increased and the plasticity will be reduced, and the strength-plasticity matching will be unreasonable. At the same time, the rolling stability of the finishing rolling unit will be reduced, and the difficulty of controlling the thickness accuracy, width accuracy and cross-sectional shape of the steel strip will increase. In serious cases, the scrap steel strip will be rolled and the equipment will be damaged. Taking the above factors into consideration, the finishing rolling temperature of the embodiment of the present invention is controlled to be 860-900℃.
[0077] The thickness of the hot-rolled steel strip obtained by the finish rolling is 1.5-4.0 mm, the finish rolling adopts a 7-stand finish rolling unit, and the cumulative reduction rate of the finish rolling is 90-94.3%.
[0078] It has been found in practice that if the cumulative reduction rate of finishing rolling is too small, uneven grains will occur, which will correspondingly reduce the plasticity of the finished steel strip. If the cumulative reduction rate of finishing rolling is too large, the deformation resistance and load of each frame of the finishing rolling unit will increase, leading to equipment hidden dangers. Taking the above factors into consideration, the cumulative reduction rate of finishing rolling is determined to be 90-94.3%.
[0079] Among them, the finishing rolling adopts a 7-stand finishing rolling unit which depends on the actual equipment configuration, and the thickness of the finished steel strip is 1.5-4.0mm which is selected by the user.
[0080] Among them, step S005 cools the hot-rolled steel strip and coils the cooled hot-rolled steel strip into a steel coil. Specifically, the hot-rolled steel strip transported on the laminar cooling roller is cooled; and the coiling temperature is controlled to be 170-210°C, and the cooled hot-rolled steel strip is coiled into a steel coil by a coiler.
[0081] The cooling treatment of the hot rolled steel strip transported on the laminar cooling roller is specifically as follows:
[0082] The hot-rolled steel strip transported on the laminar cooling roller is subjected to the first stage of water cooling at a cooling rate of ≥110°C / S to cool the steel strip to 660-690°C; after air cooling for 3-5S, the air-cooled steel strip is subjected to the second stage of water cooling at a cooling rate of ≥100°C / S.
[0083] It has been found in practice that, under the premise of a certain length of laminar cooling roller, if the cooling rate in the first stage is too low, the subsequent cooling process cannot be performed, and the desired organization and performance cannot be obtained. Therefore, the cooling rate in the first stage should be increased as much as possible. If the end temperature of the first stage water cooling is too high or too low, it cannot guarantee the formation of sufficient ferrite in the microstructure of the steel strip. If the air cooling time is too long or too short, a microstructure with a suitable ratio of ferrite and martensite cannot be obtained. If the cooling rate in the second stage is too low, martensite may not be formed in the microstructure of the steel strip. Therefore, the cooling rate in the second stage should be increased as much as possible. If the coiling temperature of the steel strip is higher than 210°C, the supercooled austenite cannot be transformed into martensite. If the coiling temperature is lower than 170°C, it will be more difficult to control the plate shape and coil shape of the steel strip. Taking the above factors into consideration, it is determined that the first-stage cooling rate of the hot-rolled steel strip on the laminar cooling roller of the embodiment of the present invention is ≥110°C / S, the temperature after the first-stage water cooling is 660-690°C, the air cooling time is 3-5S, the second-stage cooling rate is ≥100°C / S, and the coiling temperature is 170-210°C.
[0084] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods without specific conditions in the following examples are based on conventional methods and conditions.
[0085] The preparation methods of Examples 1 to 3 of the present invention include the following steps:
[0086] Firstly, the continuous casting billet is obtained through the desulfurization of molten iron pretreatment, top and bottom composite blowing converter smelting, LF refining and slab continuous casting.
[0087] The chemical composition of the continuous casting slabs obtained in Examples 1-3 of the present invention and the chemical composition of the continuous casting slabs obtained in Comparative Examples 1-3 are compared in Table 1.
[0088] Table 1 Chemical composition of the continuous casting slabs of Examples 1-3 of the present invention and the chemical composition of the continuous casting slabs of Comparative Examples 1-3 (mass percentage)
[0089]
[0090] Secondly, the continuous casting billet is heated, rough rolled, finished rolled, and cooled to obtain a hot-rolled steel strip, and the hot-rolled steel coil is obtained by coiling; wherein, in each process, the process parameters used in Examples 1 to 3 of the present invention and the process parameters used in Comparative Examples 1 to 3 are shown in Tables 2-3. The performance parameters of the steel coils of Examples 1 to 3 obtained according to the chemical composition of Table 1 and the process parameters of Tables 2-3, and the performance parameters of the steel coils of Comparative Examples 1 to 3 obtained according to the chemical composition of Table 1 and the process parameters of Tables 2-3 are shown in Table 4.
[0091] Table 2 Heating and rough rolling process parameters of Examples 1-3 of the present invention and heating and rough rolling process parameters of Comparative Examples 1-3
[0092]
[0093] Table 3 Finishing rolling, cooling and coiling process parameters of Examples 1-3 of the present invention and Comparative Examples 1-3
[0094]
[0095] Table 4 Performance of Examples 1-3 of the present invention and Performance of Comparative Examples 1-3
[0096]
[0097] As can be seen from Tables 1-4, there are significant differences in the chemical composition, heating, rough rolling, finishing rolling, cooling, coiling and other process parameters between Examples 1-3 of the present invention and Comparative Examples 1-3, and there are also significant differences in the microstructure and various properties of the steel coils obtained. The steel coils prepared by the embodiments of the present invention can better meet the new requirements for the development of photovoltaic brackets such as high strength, light weight, high hole expansion, high corrosion resistance, long life, easy manufacturing, low cost, high efficiency, free painting, maintenance-free, energy saving, and environmental protection.
[0098] The preparation method of the embodiment of the present invention optimizes the content of elements such as C, Si, Mn, P, S, Cu, Cr, Ti, and Alt, and controls C+2P, the temperature of the continuous casting billet out of the furnace and the residence time in the furnace, the start and end rolling temperature of the rough rolling, the rolling pass, the thickness of the billet, the cumulative reduction rate, the start and end rolling temperature of the finishing rolling, the rolling pass, the thickness of the finished product, the cumulative reduction rate, the cooling method, and the coiling temperature, so that the microstructure of the finished steel material is composed of 70-90% ferrite and 1 The obtained finished steel has a yield strength of ≥550MPa, a tensile strength of ≥650MPa, a yield strength ratio of ≤0.80, an elongation after fracture of ≥25%, and a corrosion rate of ≤28% relative to Q355B ordinary steel after periodic immersion in a NaHSO3 solution with an initial concentration of 0.01mol / L for 72 hours; the straight seam electric welded steel pipe processed by the steel coil of the embodiment of the present invention has no cracks in the base material during the 60° expansion test, such as Figure 2 shown.
[0099] The high-expansion low-alloy corrosion-resistant steel coil for the photovoltaic bracket of the embodiment of the present invention does not contain Sb, has low content of other harmful and impurity elements, and has pure steel. It has high strength and can reduce weight by 26% by replacing Q235B galvanized sheet, with a significant lightweight effect. It has strong corrosion resistance and can meet the service requirements of photovoltaic brackets. It has excellent forming performance and can meet the demanding processing requirements of photovoltaic brackets. It has a low yield strength ratio, small springback when manufacturing photovoltaic bracket accessories, easy forming, large plastic reserve of photovoltaic bracket, good seismic and external impact resistance, and large safety margin. The P and Al contents are moderate, and the Cu and Ti contents are low, which avoids their adverse effects on plasticity, welding performance, surface quality, etc., and has stable mechanical properties, low manufacturing difficulty, and high production efficiency. It does not contain precious alloy elements such as Ni, Nb, V, Mo, etc., has a low Mn content, and has a low alloy cost. No need for post-pickling, painting and maintenance, energy saving, environmental protection, short delivery cycle, and low cost of use.
[0100] The high-expansion low-alloy corrosion-resistant steel coil for photovoltaic brackets in the embodiments of the present invention can better meet the new requirements for the development of photovoltaic brackets such as high strength, light weight, high-expansion, high corrosion resistance, long life, easy manufacturing, low cost, high efficiency, painting-free, maintenance-free, energy-saving, and environmental protection.
[0101] An embodiment of the present invention further provides a steel coil for a photovoltaic support, which is prepared by the preparation method of any one of the above embodiments.
[0102] The microstructure of the steel coil is ferrite and martensite, with ferrite accounting for 70-90% and martensite accounting for 10-30%;
[0103] The yield strength of the steel coil is ≥550MPa, the tensile strength is ≥650MPa, the yield strength ratio is ≤0.80, the elongation after fracture is ≥25%, and the 180°d=a cold bending test is qualified;
[0104] After the steel coil is periodically immersed in a NaHSO3 solution with an initial concentration of 0.01 mol / L for 72 hours, the corrosion rate relative to Q355B ordinary steel is ≤28%;
[0105] The straight seam electric welded steel pipe sample processed by the steel coil of the embodiment of the present invention has no cracks in the base material during the 60° expansion test. Figure 2 shown.
[0106] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. The present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A method for preparing a steel coil for a photovoltaic support, characterized in that: include: Obtaining a continuous casting billet through pretreatment; Heating and heat-insulating the continuous casting billet; Rough rolling the continuous casting billet using a rough rolling mill to obtain a strip billet; The strip is finish-rolled by a finishing mill to obtain a hot-rolled steel strip; as well as Cooling the hot-rolled steel strip, and coiling the cooled hot-rolled steel strip into a steel coil; Wherein, the continuous casting billet comprises the following components by mass percentage: C: 0.08%-0.10%, Si: 0.55%-0.64%, Mn: 0.51%-0.60%, P: 0.056%-0.065%, S: 0.0050%-0.0060%, Cu: 0.13%-0.18%, Cr: 2.8%-3.0%, Ti: 0.026%-0.035%, Alt: 0.17%-0.20%, and the rest are Fe and unavoidable impurities, and the continuous casting billet also needs to satisfy C+2P≤0.30%.
2. The preparation method according to claim 1, characterized in that: The continuous casting billet obtained by pretreatment specifically comprises: obtaining the continuous casting billet through molten iron pretreatment desulfurization, top and bottom composite blowing converter smelting, LF refining and slab continuous casting; the thickness of the continuous casting billet is 180-230 mm.
3. The preparation method according to claim 1, characterized in that: The heating and insulation treatment of the continuously cast billet further includes: loading the continuously cast billet into a walking-beam heating furnace; and heating and insulation treatment of the continuously cast billet in the walking-beam heating furnace; wherein the furnace discharge temperature of the continuously cast billet is 1190-1210°C, and the cumulative furnace residence time of the continuously cast billet is 180-210 minutes.
4. The preparation method according to claim 1, characterized in that: The step of using a rough rolling mill to perform rough rolling on the continuous casting billet to obtain a strip billet comprises: controlling the starting rolling temperature of the rough rolling to be 1140-1160° C., the final rolling temperature of the rough rolling to be 1070-1110° C., and using a rough rolling mill to perform rough rolling on the continuous casting billet to obtain a strip billet; The thickness of the strip obtained by the rough rolling is 28-40 mm, the number of rough rolling passes is 7, and the cumulative reduction rate of the rough rolling is 82.6-87.8%.
5. The preparation method according to claim 1, characterized in that: The method of using a finishing mill to finish-roll the strip to obtain a hot-rolled steel strip comprises: controlling the start rolling temperature of the finishing rolling to be 1010-1060° C., the final rolling temperature of the finishing rolling to be 860-900° C., and using a finishing mill to finish-roll the strip to obtain a hot-rolled steel strip; The thickness of the hot-rolled steel strip obtained by the finish rolling is 1.5-4.0 mm, the finish rolling adopts a 7-stand finish rolling unit, and the cumulative reduction rate of the finish rolling is 90-94.3%.
6. The preparation method according to claim 1, characterized in that: The cooling treatment of the hot-rolled steel strip and coiling the cooled hot-rolled steel strip into a steel coil specifically comprises: cooling the hot-rolled steel strip transported on a laminar cooling roller; and controlling the coiling temperature to be 170-210° C. and coiling the cooled hot-rolled steel strip into a steel coil using a coiler.
7. The preparation method according to claim 6, characterized in that: The cooling treatment of the hot-rolled steel strip transported on the laminar cooling roller is specifically as follows: The hot-rolled steel strip transported on the laminar cooling roller is subjected to the first stage of water cooling at a cooling rate of ≥110°C / S to cool the steel strip to 660-690°C; after air cooling for 3-5S, the air-cooled steel strip is subjected to the second stage of water cooling at a cooling rate of ≥100°C / S.
8. A steel coil for photovoltaic support, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 7.
9. The steel coil according to claim 8, characterized in that: The microstructure of the steel coil is ferrite and martensite, wherein the proportion of ferrite is 70-90% and the proportion of martensite is 10-30%.
10. The steel coil according to claim 8, characterized in that: After the steel coil is periodically immersed in a NaHSO3 solution with an initial concentration of 0.01 mol / L for 72 hours, the corrosion rate relative to Q355B ordinary steel is ≤28%; The straight seam electric welded steel pipe processed from the steel coil has no cracks in the base material during the 60° expansion test.
Citation Information
Patent Citations
Welding structure fire-resistant and weather-resistant steel with yield strength being 550 MPa or above and production method
CN108754335A
High-strength weathering steel for photovoltaic support and preparation method of high-strength weathering steel
CN115786822A
High-corrosion-resistance 670MPa-grade hot-rolled weather-resistant steel plate for photovoltaic support and preparation method of hot-rolled weather-resistant steel plate
CN117488209A
Preparation method of 1.5 mm hot-rolled high-strength weather-resistant photovoltaic support steel
CN117583387A
High-strength weathering steel for photovoltaic bracket and method for preparing thin steel plate from high-strength weathering steel
CN118374748A
